Mindfulness and skills-based eHealth intervention to reduce distress in cancer-affected patients in the Reduct trial: Intervention protocol of the make it training optimized - Heinen, Jana; Bäuerle, Alexander; Schug, Caterina; Krakowczyk, Julia Barbara; Strunk, Sven Erik; Wieser, Alexandra; Beckord, Jil; Jansen, Christoph; Dries, Sebastian; Pantförder, Michael; Erim, Yesim; Zipfel, Stephan; et al. (Frontiers in Psychiatry, 2022)
Introduction: Cancer-affected patients experience high distress and have an elevated risk of developing mental disorders due to various burdens. So far, many cancer patients do not receive adequate psycho-oncological support. One way to expand psycho-oncological support is through digital interventions. This protocol describes the development and structure of a web-based psycho-oncological intervention, the Make It Training optimized. This intervention is currently evaluated in the Reduct trial, a multicenter randomized controlled trial. Methods: The Make It Training optimized was developed in six steps: A patient need and demand assessment, development and acceptability analysis of a prototype, the formation of a patient advisory council, the revision of the training, implementation into a web app, and the development of a motivation and evaluation plan. Results: Through a process of establishing cancer-affected patients’ needs, prototype testing, and patient involvement, the Make It Training optimized was developed by a multidisciplinary team and implemented in a web app. It consists of 16 interactive self-guided modules which can be completed within 16 weeks. Discussion: Intervention protocols can increase transparency and increase the likelihood of developing effective web-based interventions. This protocol describes the process and results of developing a patient-oriented intervention. Future research should focus on the further personalization of web-based psycho-oncological interventions and the potential benefits of combining multiple psychotherapeutic approaches.